2008
DOI: 10.2741/3112
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assays of molecular motors - impact of motor-surface interactions

Abstract: In many types of biophysical studies of both single molecules and ensembles of molecular motors the motors are adsorbed to artificial surfaces. Some of the most important assay systems of this type (in vitro motility assays and related single molecule techniques) will be briefly described together with an account of breakthroughs in the understanding of actomyosin function that have resulted from their use. A poorly characterized, but potentially important, entity in these studies is the mechanism of motor ads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 52 publications
(97 reference statements)
4
38
0
Order By: Relevance
“…As a result of this mode of adsorption, the heads may extend appreciably away from the surface (Albet-Torres et al 2010; Persson et al 2010). This configuration is believed to completely dominate on moderately hydrophobic surfaces (TMCS) whereas the available evidence is consistent with HMM adsorption to pure glass/SiO 2 , preferably via positively charged loops in the actin binding region (Albet-Torres et al 2010; Månsson et al 2008; Persson et al 2010). This idea is consistent with high-speed atomic force microscopy images (Ando et al 2001a; for movies see Ando et al 2001b) where myosin V is imaged while adsorbed to freshly cleaved mica[a silicate mineral with, generally low contact angle and negative surface charge (Yang et al 2007)].…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 68%
See 2 more Smart Citations
“…As a result of this mode of adsorption, the heads may extend appreciably away from the surface (Albet-Torres et al 2010; Persson et al 2010). This configuration is believed to completely dominate on moderately hydrophobic surfaces (TMCS) whereas the available evidence is consistent with HMM adsorption to pure glass/SiO 2 , preferably via positively charged loops in the actin binding region (Albet-Torres et al 2010; Månsson et al 2008; Persson et al 2010). This idea is consistent with high-speed atomic force microscopy images (Ando et al 2001a; for movies see Ando et al 2001b) where myosin V is imaged while adsorbed to freshly cleaved mica[a silicate mineral with, generally low contact angle and negative surface charge (Yang et al 2007)].…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 68%
“…2). (Albet-Torres et al 2010; Månsson 2010; Månsson et al 2008; Sundberg et al 2006a; Vikhoreva and Månsson 2010). In contrast, the total HMM density on the different surfaces did not appear to differ appreciably.…”
Section: Developments From 2005 and Onwardsmentioning
confidence: 99%
See 1 more Smart Citation
“…(38) With regard to HMM, in particular, it has been indicated that freezing in solution at −20 °C for later use in the IVMA is not advisible, even if glycerol is added as a cryoprotecting agent. 36,39 This may be understood because some regions of the HMM molecule exhibit conformational instability (cf.ref (6)) whereas other regions are sensitive to oxidation. The good preservation of function in the present work may, to a substantial degree, be attributed to factors related to the surface immobilization of the proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The actomyosin motor system relies on intact enzymatic function, actin polymerization, and actomyosin bimolecular interactions, and it is sensitive to deterioration by several mechanisms. 46 It should therefore be a critical test system for investigations of functional changes during storage.…”
Section: Introductionmentioning
confidence: 99%